2015
DOI: 10.1016/j.chb.2015.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personality types in software tasks choices

Abstract: Abstract-According to psychology, not everybody can excel at all kinds of tasks. Thus, chances of a successful outcome of software development increase if people with particular personality traits are assigned to their preferred tasks in the project. Likewise, software development depends significantly on how software practitioners perform their tasks. This empirical study surveys 100 Cuban software developers, both students and professors of the University of Informatics Sciences in Havana, Cuba. This work ai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…Moreover, an ethnographic study targeting the actualization of MBTI measures on software teams by Karn and Cowling [38] reached a conclusion that specific personality types are more gravitated towards some specific type of development activities, as well as some specific roles. A recent empirical study suggests that there is a pattern that connects personality characteristics to role choices in software development activities where assigning tasks to individuals regarding personality types improves the chance of success [39].…”
Section: Personality Research In Software Engineeringmentioning
confidence: 99%
“…Moreover, an ethnographic study targeting the actualization of MBTI measures on software teams by Karn and Cowling [38] reached a conclusion that specific personality types are more gravitated towards some specific type of development activities, as well as some specific roles. A recent empirical study suggests that there is a pattern that connects personality characteristics to role choices in software development activities where assigning tasks to individuals regarding personality types improves the chance of success [39].…”
Section: Personality Research In Software Engineeringmentioning
confidence: 99%
“…In a recent empirical study, Capretz et al [32] indicated that personality characteristics are related to role choices in software development activities. Therefore, it shows that team performance might be improved by regarding personality types when assigning responsibilities to team members.…”
Section: Personality Research In Software Engineeringmentioning
confidence: 99%
“…A plethora of research has been carried out in the past to explore the key importance of team composition and personality types in software development . However, the personality types that are useful and beneficial for ideal and effective teamwork are still not well defined for practitioners and researchers . Further, the results, extracted from different theoretical personality models, have produced contradictory fits, validity challenges, and missing guidance for software development personnel selection.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, the personality types that are useful and beneficial for ideal and effective teamwork are still not well defined for practitioners and researchers. [15][16][17][18] Further, the results, extracted from different theoretical personality models, have produced contradictory fits, validity challenges, and missing guidance for software development personnel selection. For instance, according to da Silva et al, 19 different results were obtained when models were used in practice to compose teams.…”
mentioning
confidence: 99%